Prevalence and mortality due to acute kidney injuries in patients with influenza A (H1N1) viral infection: A systemic narrative review - Al Dalbhi, Sultan; Alshahrani, Hassan Ali; Almadi, Ahmad; Busaleh, Hamza; Alotaibi, Mohammed; Almutairi, Wejdan; Almukhrq, Zahra (International Journal of Health Sciences, 2019)
Introduction: There is limited evidence of studying the associated factors of acute kidney injury (AKI) among patients with influenza A (H1N1) virus infection pandemic in 2009. AKI is one of the most prevalent complications in the intensive care unit. Its incidence is associated with high mortality and negative impacts on long-term survival. The aim of this narrative review was to determine the prevalence and mortality due to AKI, among patients admitted with the H1N1 virus. Materials and Methods: A narrative review of studies reporting about treatment measures and mortality associated with AKI during the H1N1 pandemic over a 10-year period (from September 2009 to August 2018), was performed. We searched the following databases; EMBASE, Medline/PubMed, NHS evidence, Google Scholar, and the Cochrane Library. Our inclusion revealed 20 studies of patients (n = 3579) who were admitted with H1N1 infection and developed AKI. Results: In this study, 33% of patients (n = 1164) who were admitted with H1N1 infection had developed AKI. Within the first 5 years (2009 to 2013), 36% of patients (n = 1013) developed AKI. Within the next 5 years (2014–2018), 812 patients were admitted with the H1N1 infection and 18% of patients (n = 150) had developed AKI. Over the 10 years, there was a 50% reduction in the number of patients who developed AKI (2009 and 2018) (P < 0.0001). Conclusion: Patients showed varied responses to treatment measures, depending on their geographical location, comorbidities, and other characteristics. Despite a reasonable prevalence of AKI among patients with the H1N1 virus infection, the mortality over the last 10 years was reduced, with renal replacement therapy as a common therapy in most studies.